UV-enhanced environmental charge compensation in near ambient pressure XPS - Müller, Hendrik; Weinberger, Christian; Grundmeier, Guido; de los Arcos de Pedro, Maria Teresa (Journal of Electron Spectroscopy and Related Phenomena)
Keywords: Physical and Theoretical Chemistry; Spectroscopy; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Radiation; Electronic; Optical and Magnetic Materials

Adsorption of Ferritin at Nanofaceted Al2O3 Surfaces - Pothineni, Bhanu K.; Kollmann, Sabrina; Li, Xinyang; Grundmeier, Guido; Erb, Denise J.; Keller, Adrian (International Journal of Molecular Sciences)
The influence of nanoscale surface topography on protein adsorption is highly important for numerous applications in medicine and technology. Herein, ferritin adsorption at flat and nanofaceted, single-crystalline Al2O3 surfaces is investigated using atomic force microscopy and X-ray photoelectron spectroscopy. The nanofaceted surfaces are generated by the thermal annealing of Al2O3 wafers at temperatures above 1000 °C, which leads to the formation of faceted saw-tooth-like surface topographies with periodicities of about 160 nm and amplitudes of about 15 nm. Ferritin adsorption at these nanofaceted surfaces is notably suppressed compared to the flat surface at a concentration of 10 mg/mL, which is attributed to lower adsorption affinities of the newly formed facets. Consequently, adsorption is restricted mostly to the pattern grooves, where the proteins can maximize their contact area with the surface. However, this effect depends on the protein concentration, with an inverse trend being observed at 30 mg/mL. Furthermore, different ferritin adsorption behavior is observed at topographically similar nanofacet patterns fabricated at different annealing temperatures and attributed to different step and kink densities. These results demonstrate that while protein adsorption at solid surfaces can be notably affected by nanofacet patterns, fine-tuning protein adsorption in this way requires the precise control of facet properties.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Investigation of the Compatibility between Warheads and Peptidomimetic Sequences of Protease Inhibitors—A Comprehensive Reactivity and Selectivity Study - Müller, Patrick; Meta, Mergim; Meidner, Jan Laurenz; Schwickert, Marvin; Meyr, Jessica; Schwickert, Kevin; Kersten, Christian; Zimmer, Collin; Hammerschmidt, Stefan Josef; Frey, Ariane; Lahu, Albin; de la Hoz-Rodríguez, Sergio; et al. (International Journal of Molecular Sciences)
Covalent peptidomimetic protease inhibitors have gained a lot of attention in drug development in recent years. They are designed to covalently bind the catalytically active amino acids through electrophilic groups called warheads. Covalent inhibition has an advantage in terms of pharmacodynamic properties but can also bear toxicity risks due to non-selective off-target protein binding. Therefore, the right combination of a reactive warhead with a well-suited peptidomimetic sequence is of great importance. Herein, the selectivities of well-known warheads combined with peptidomimetic sequences suited for five different proteases were investigated, highlighting the impact of both structure parts (warhead and peptidomimetic sequence) for affinity and selectivity. Molecular docking gave insights into the predicted binding modes of the inhibitors inside the binding pockets of the different enzymes. Moreover, the warheads were investigated by NMR and LC-MS reactivity assays against serine/threonine and cysteine nucleophile models, as well as by quantum mechanics simulations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu; Huang, Jingyuan; Dornbusch, Daniel; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian; Cheung, David L. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate - Hanke, Marcel; Hansen, Niklas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation time. Using DNA origami nanostructures as sensors that translate small molecular transitions into nanostructural changes, the denaturing effects of the Gdm salts were directly visualized by atomic force microscopy. GdmSCN was the most potent DNA denaturant, which caused complete DNA origami denaturation at 50 °C already at a concentration of 2 M. Under such harsh conditions, denaturation occurred within the first 15 min of Gdm exposure, whereas much slower kinetics were observed for the more weakly denaturing salt Gdm2SO4 at 25 °C. Lastly, we observed a novel non-monotonous temperature dependence of DNA origami denaturation in Gdm2SO4 with the fraction of intact nanostructures having an intermediate minimum at about 40 °C. Our results, thus, provide further insights into the highly complex Gdm–DNA interaction and underscore the importance of the counteranion species.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Synthesis and Characterization of Catalytically Active Au Core─Pd Shell Nanoparticles Supported on Alumina - Feng, Yanyue; Schaefer, Andreas; Hellman, Anders; Di, Mengqiao; Härelind, Hanna; Bauer, Matthias; Carlsson, Per-Anders (Langmuir)
A two-step seeded-growth method was refined to synthesize Au@Pd core@shell nanoparticles with thin Pd shells, which were then deposited onto alumina to obtain a supported Au@Pd/Al2O3 catalyst active for prototypical CO oxidation. By the strict control of temperature and Pd/Au molar ratio and the use of l-ascorbic acid for making both Au cores and Pd shells, a 1.5 nm Pd layer is formed around the Au core, as evidenced by transmission electron microscopy and energy-dispersive spectroscopy. The core@shell structure and the Pd shell remain intact upon deposition onto alumina and after being used for CO oxidation, as revealed by additional X-ray diffraction and X-ray photoemission spectroscopy before and after the reaction. The Pd shell surface was characterized with in situ infrared (IR) spectroscopy using CO as a chemical probe during CO adsorption–desorption. The IR bands for CO ad-species on the Pd shell suggest that the shell exposes mostly low-index surfaces, likely Pd(111) as the majority facet. Generally, the IR bands are blue-shifted as compared to conventional Pd/alumina catalysts, which may be due to the different support materials for Pd, Au versus Al2O3, and/or less strain of the Pd shell. Frequencies obtained from density functional calculations suggest the latter to be significant. Further, the catalytic CO oxidation ignition-extinction processes were followed by in situ IR, which shows the common CO poisoning and kinetic behavior associated with competitive adsorption of CO and O2 that is typically observed for noble metal catalysts.
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

High resolution off resonant spectroscopy as a probe of the oxidation state - Nowakowski, Michal; Kalinko, Aleksandr; Szlachetko, Jakub; Fanselow, Rafał; Bauer, Matthias (Journal of Analytical Atomic Spectrometry)
The direct conversion between HEROS-XES and XANES edge position (E0) without need of measuring absorption spectra.
Keywords: Spectroscopy; Analytical Chemistry

High resolution off resonant spectroscopy as a probe of the oxidation state - Nowakowski, Michał; Kalinko, Aleksandr; Szlachetko, Jakub; Fanselow, Rafał; Bauer, Matthias (Journal of Analytical Atomic Spectrometry)
Currently, chemistry and physics are strongly dependent on the concept of the oxidation state. While the formal oxidation state is easily evaluated, the real physical oxidation state value is often difficult to determine and significantly varies from the formal values. Determination of the ionization threshold in X-ray absorption spectroscopy (XANES) relies on the absorption edge position and sometimes poses limitations, mainly due to the edge resonances. Moreover, the lower energy states can be probed only within x-soft or XUV photons providing only surface state information of probed materials. Here, we employ high energy resolution off-resonant spectroscopy to determine both 1s and 3p binding energies of Fe-based materials and therefore correlate to their physical oxidation state. The results are compared to the ones obtained with classical X-ray absorption, X-ray emission, and photoelectron spectroscopies. The observed differences in binding energies are discussed in a frame of initial and final state interactions with the atom's electronic configurations. The presented methodology is discussed towards potential use to single-shot experiments and application at X-ray free-electron lasers. Alternatively, core level X-ray emission spectroscopy can be used, but the emission line positions are strongly affected by spin-orbit interaction. However, due to the energy transfer from the photon to the excited core electron, the same information as in XANES is probed in high energy resolution off-resonant spectroscopy (HEROS). Based on the Kramers–Heisenberg theory, we propose a new approach for ionization threshold determination which is free of the limitations encountered in XANES-based determination of the core state energy. Namely, the value of core state energy can be determined analytically using a few HEROS spectra recorded with significantly higher spectral resolution. This approach provides a basis for the universal physical oxidation state determination method.
Keywords: Spectroscopy; Analytical Chemistry

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)
Keywords: Spectroscopy; General Materials Science

Correlating facet orientation, defect-level density and dipole layer formation at the surface of polycrystalline CuInSe2 thin films - Elizabeth, Amala; Conradi, Hauke; K. Sahoo, Sudhir; Kodalle, Tim; A. Kaufmann, Christian; Kühne, Thomas; Mirhosseini, Hossein; Abou-Ras, Daniel; Mönig, Harry (Acta Materialia)
Individual grains of chalcopyrite solar cell absorbers can facet in different crystallographic directions at their surfaces. To gain a deeper understanding of the junction formation in these devices, we correlate variations in the surface facet orientation with the defect electronic properties. We use a combined analytical approach based on scanning tunneling spectroscopy (STS), scanning electron microscopy, and electron back scatter diffraction (EBSD), where we perform these experiments on identical surface areas as small as 2 × 2 µm2 with a lateral resolution well below 50 nm. The topography of the absorber surfaces indicates two main morphological features: micro-faceted, long basalt-like columns and their short nano-faceted terminations. Our STS results reveal that the long columns exhibit spectral signatures typical for the presence of pronounced oxidation-induced surface dipoles in conjunction with an increased density of electronic defect levels. In contrast, the nano-faceted terminations of the basalt-like columns are largely passivated in terms of electronic defect levels within the band gap region. Corresponding crystallographic data based on EBSD experiments show that the surface of the basalt-like columns can be assigned to intrinsically polar facet orientations, while the passivated terminations are assigned to non-polar planes. Ab-initio calculations suggest that the polar surfaces are more prone to oxidation and resulting O-induced defects, in comparison to non-polar planes. Our results emphasize the correlation between morphology, surface facet orientations and surface electronic properties. Furthermore, this work aids in gaining a fundamental understanding of oxidation induced lateral inhomogeneities in view of the p-n junction formation in chalcopyrite thin-film solar cells.
Keywords: Chalcopyrite absorber; Scanning tunneling spectroscopy; Electron backscatter diffraction; Density functional theory; Surface dipole

Water structure near the surface of Weyl semimetals as catalysts in photocatalytic proton reduction - Gujt, Jure; Zimmer, Peter; Zysk, Frederik; Süß, Vicky; Felser, Claudia; Bauer, Matthias; Kühne, Thomas (Structural Dynamics)
Keywords: Spectroscopy; Condensed Matter Physics; Instrumentation; Radiation

Thin films of poly(vinylidene fluoride-co-hexafluoropropylene)-ionic liquid mixtures as amperometric gas sensing materials for oxygen and ammonia - Lee, Junqiao; Hussain, Ghulam; Lopez Salas, Nieves; MacFarlane, Douglas R.; Silvester, Debbie S. (The Analyst)
A gas sensor comprising of a planar electrode device covered with a thin layer of gel polymer electrolyte gave accurate and fast sensing responses for oxygen and ammonia detection in both the cathodic and anodic potential regions.
Keywords: Electrochemistry; Spectroscopy; Environmental Chemistry; Biochemistry; Analytical Chemistry

Controlling Self-Assembly with Light and Temperature - Carl, Nico; Müller, Wenke; Schweins, Ralf; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Self-Assembly of Fibrinogen in Aqueous, Thrombin-Free Solutions of Variable Ionic Strengths - Hämisch, Benjamin; Büngeler, Anne; Kielar, Charlotte; Keller, Adrian; Strube, Oliver; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Secondary Particle Formation during the Nonaqueous Synthesis of Metal Oxide Nanocrystals - Stolzenburg, Pierre; Hämisch, Benjamin; Richter, Sebastian; Huber, Klaus; Garnweitner, Georg (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

The Role of Electronic and Phononic Excitation in the Optical Response of Monolayer WS2 after Ultrafast Excitation - Ruppert, Claudia; Chernikov, Alexey; Hill, Heather M.; Rigosi, Albert F.; Heinz, Tony F. (Nano Letters)
Transient changes of the optical response of WS2 monolayers are studied by femtosecond broadband pump–probe spectroscopy. Time-dependent absorption spectra are analyzed by tracking the line width broadening, bleaching, and energy shift of the main exciton resonance as a function of time delay after the excitation. Two main sources for the pump-induced changes of the optical response are identified. Specifically, we find an interplay between modifications induced by many-body interactions from photoexcited carriers and by the subsequent transfer of the excitation to the phonon system followed by cooling of the material through the heat transfer to the substrate.
Keywords: Atomically thin 2D materials; carrier and phonon dynamics; ultrafast spectroscopy

Silica Polymerization from Supersaturated Dilute Aqueous Solutions in the Presence of Alkaline Earth Salts - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Insight into the Final Step of the Supramolecular Buildup of Eumelanin - Büngeler, Anne; Hämisch, Benjamin; Huber, Klaus; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Joint Raman spectroscopy and HRXRD investigation of cubic gallium nitride layers grown on 3C-SiC - Rüsing, Michael; Wecker, T.; Berth, Gerhard; As, Donat Josef; Zrenner, Artur (physica status solidi (b))
Cubic gallium nitride (GaN) films are analyzed with highresolution X-ray diffraction (HRXRD) and Raman spectroscopy. Several cubic GaN layers were grown on 3C-SiC (001) substrate by radio-frequency plasma-assisted molecular beam epitaxy. The layer thickness of the cubic GaN was varied between 75 and 505 nm. The HRXRD analysis reveals a reduction of the full-width at half-maximum (FWHM) of omega scans for growing layer thicknesses, which is caused by a partial compensation of defects. The Raman characterization confirms well-formed c-GaN layers. A more detailed examination of the longitudinal optical mode hints at a correlation of the FWHM of the Raman mode with the dislocation density, which shows the possibility to determine dislocation densities by Ramanspectroscopy on a micrometer scale, which is not possible by HRXRD. Furthermore, this Raman analysis shows that normalized Raman spectra present an alternative way to determine layer thicknesses of thin GaN films.
Keywords: cubic gallium nitride; dislocation density; HRXRD; Raman spectroscopy

Gelled Lyotropic Liquid Crystals - Xu, Yang; Laupheimer, Michaela; Preisig, Natalie; Sottmann, Thomas; Schmidt, Claudia; Stubenrauch, Cosima (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Use of Eutectic Mixtures for Preparation of Monolithic Carbons with CO2-Adsorption and Gas-Separation Capabilities - Lopez Salas, Nieves; Jardim, E. O.; Silvestre-Albero, A.; Gutiérrez, M. C.; Ferrer, M. L.; Rodríguez-Reinoso, F.; Silvestre-Albero, J.; del Monte, F. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Mechanistic Studies of Silica Polymerization from Supersaturated Aqueous Solutions by Means of Time-Resolved Light Scattering - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Structural Evolution in the Isotropic Channel of a Water–Nonionic Surfactant System That Has a Disconnected Lamellar Phase: A 1H NMR Self-Diffusion Study - Stubenrauch, Cosima; Kleinschmidt, Felix; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Impact of Sodium Polyacrylate on the Amorphous Calcium Carbonate Formation from Supersaturated Solution - Liu, J.; Pancera, S.; Boyko, V.; Gummel, J.; Nayuk, R.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Imaging of the Ferroelectric Domain Structures by Confocal Raman Spectroscopy - Berth, Gerhard; Hahn, Wjatscheslaw; Wiedemeier, Volker; Zrenner, Artur; Sanna, Simone; Schmidt, Wolf Gero (Ferroelectrics)
Confocal Raman spectroscopy was performed as an archetype imaging method to study the ferroelectric domain structure of periodically poled lithium niobate. More precisely, the linkage out of spatial resolution and spectral information proved itself as very useful. Here a specific modulation of the Raman lines by the local variation of polarity and a non-symmetric measuring-signal across the domain structure were found, which allows for imaging of domain boundaries as well as oppositely orientated domains. The high potential of this method is demonstrated by the visualization of the ferroelectric domain structures based on various phonon modes.
Keywords: Raman spectroscopy; ferroelectric domains; LiNbO3; confocal imaging

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Exposure of [MnIII6CrIII]3+ single-molecule magnets to soft X-rays: The effect of the counterions on radiation stability - Helmstedt, Andreas; Sacher, Marc; Gryzia, Aaron; Harder, Alexander; Brechling, Armin; Müller, Norbert; Heinzmann, Ulrich; Hoeke, Veronika; Krickemeyer, Erich; Glaser, Thorsten; Bouvron, Samuel; Fonin, Mikhail (Journal of Electron Spectroscopy and Related Phenomena)
Keywords: Physical and Theoretical Chemistry; Spectroscopy; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Radiation; Electronic; Optical and Magnetic Materials

Size Determination of Shear-Induced Multilamellar Vesicles by Rheo-NMR Spectroscopy - Medronho, B.; Schmidt, Claudia; Olsson, U.; Miguel, M. G. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Defect Formation in a Nonionic Lamellar Phase - Medronho, B.; Rodrigues, M.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Evaluation of the Particle Growth of Amorphous Calcium Carbonate in Water by Means of the Porod Invariant from SAXS - Liu, J.; Pancera, S.; Boyko, V.; Shukla, A.; Narayanan, T.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Hydrogen-Bond-Induced Heteroassembly in Binary Colloidal Systems - Bayer, Frank M.; Hiltrop, Karl; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Transitions between a Planar Lamellar Phase and Multilamellar Vesicles: Continuous versus Discontinuous Transformation - Medronho, B.; Shafaei, S.; Szopko, R.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Analysis of the Nucleation and Growth of Amorphous CaCO3 by Means of Time-Resolved Static Light Scattering - Liu, Jianing; Rieger, Jens; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Structure−Property Relationship in Stimulus-Responsive Bolaamphiphile Hydrogels - Meister, Annette; Bastrop, Martin; Koschoreck, Sven; Garamus, Vasil M.; Sinemus, Thomas; Hempel, Günter; Drescher, Simon; Dobner, Bodo; Richtering, Walter; Huber, Klaus; Blume, Alfred (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Aggregation of a Pseudoisocyanine Chloride in Aqueous NaCl Solution - Herzog, Bernd; Huber, Klaus; Stegemeyer, Horst (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Lyotropic Mesophases Next to Highly Efficient Microemulsions: A 2H NMR Study - Stubenrauch, Cosima; Frank, Christian; Strey, Reinhard; Burgemeister, Daniel; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Model of Polydisperse Wormlike Stars and Its Application to Dyestuff Aggregates - Katzenstein, Armin; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Time-Resolved Recording of Ionic Dyestuff Aggregation by Static Light Scattering - Inglés, Sergio Escudero; Katzenstein, Armin; Schlenker, Wolfgang; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced States of Orientation of the Lamellar Phase of C12E4/Water - Müller, Stefan; Börschig, Claus; Gronski, Wolfram; Schmidt, Claudia; Roux, Didier (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Alignment of a Hexagonal Lyotropic Liquid Crystal as Studied by Rheo-NMR - Lukaschek, Michail; Grabowski, David A.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science